Evaluation of non-destructive testing and long-term durability of geopolymer aggregate concrete - Udhaya Kumar, T.; Vinod Kumar, M.; Salunkhe, Sachin; Cep, Robert (Frontiers in Built Environment, 2024)
Recent advancements in concrete technology focus more on increasing strength than durability. Concrete with good durability will withstand adverse conditions like frost, chloride penetration, sulfate assault, alkali-aggregate reaction, steel corrosion, etc., which will lower the strength of the concrete. Strength is vital, but so is durability. The present study examined and discussed the durability parameters of conventional concrete made with geopolymer aggregate (GPA) as a partial substitute for natural aggregate. Strength studies in this research found that the optimal level of substitution for natural coarse aggregate by GPA was 100% replacement to produce the performing concrete. Replacement of natural coarse aggregate by geopolymer aggregate exhibits 9%–15% higher compressive strength than natural aggregate concrete. The findings reveal that concrete with 100% geopolymer aggregate exhibits a compressive strength increase of 9%–15% over that of concrete made with natural aggregates. Ultrasonic pulse velocity measurements for geopolymer aggregate concrete range between 4 km/s and 4.5 km/s, indicating good quality according to IS specifications. Additionally, Rebound Hammer test results further support the enhanced quality of geopolymer aggregate concrete. However, the porosity of geopolymer aggregates results in a sorptivity that is 10%–30% higher than that of natural aggregate concrete. Despite this, the increased resistance to acid and sulfate attacks is noted, attributed to the strong bonding between geopolymer aggregates and the cement matrix.